Infarct size and left ventricular function in the PRoximal Embolic Protection in Acute myocardial infarction and Resolution of ST-segment Elevation (PREPARE) trial: ancillary cardiovascular magnetic resonance study. Issue 3 (26th October 2009) - Haeck, J D; Kuijt, W J; Koch, K T; Bilodeau, L; Henriques, J P; Rohling, W J; Baan, J; Vis, M M; Nijveldt, R; van Geloven, N; Groenink, M; Piek, J J; et al.
Abstract : Objectives: The aim of the study was to evaluate whether primary percutaneous coronary intervention (PCI) with combined proximal embolic protection and thrombus aspiration results in smaller final infarct size and improved left ventricular function assessed by cardiovascular magnetic resonance (CMR) in ST-segment elevation myocardial infarction (STEMI) patients compared with primary PCI alone. Background: Primary PCI with the Proxis system improves immediate microvascular flow post-procedure as measured by ST-segment resolution, which could result in better outcomes. Methods: The ancillary CMR study included 206 STEMI patients who were enrolled in the PRoximal Embolic Protection in Acute myocardial infarction and Resolution of ST-Elevation (PREPARE) trial. CMR imaging was assessed between 4 and 6 months after the index procedure. Results: There were no significant differences in final infarct size (6.1 g/m 2 vs 6.3 g/m 2, p = 0.78) and left ventricular ejection fraction (50% vs 50%, p = 0.46) between both groups. Also, systolic wall thickening in the infarct area (44% vs 45%, p = 0.93) or the extent of transmural segments (8.3% of segments vs 8.3% of segments, p = 0.60) showed no significant differences. The incidence of major adverse cardiac and cerebral events at 6 months was similar in the Proxis and control group (8% vs 10%, respectively, p = 0.43). Conclusions: Primary PCI with combined proximal embolic protection and thrombus aspiration in STEMI patients did not result in significant differences in final infarct size or left ventricular function at follow-up CMR. In addition, there was no difference in the incidence of major adverse cardiac and cerebral events at 6 months. Trial registration number: ISRCTN71104460.